Сейсмічна розвідка методом хитної частоти - Анахов, П.В. (Геоінформатика, 2015)
Розглянуто нестійкість частот стоячих хвиль водойми (сейш) у різних масштабах часу — від короткочасного, порівнянного із періодом сейш, до тривалого, що цей період значно перевищує. Визначено, що частоту стоячих хвиль водного басейну у першому випадку задає фаза збуджувального коливання, у другому — глибина водойми. Запропоновано методи сейсмічної розвідки, в яких використовують хитання частот сейш — короткочасне фазомодульоване, тривале частотно-модульоване. Рассматривается нестабильность частот стоячих волн водоемов (сейш) в различных масштабах времени - от кратковременного, сопоставимого с периодом сейш, до длительного, значительно этот период превышающего. Определено, что частоту стоячих волн водного бассейна в первом случае задает фаза возбуждающего колебания, во втором - глубина водоема. Предлагаются методы сейсмической разведки, которые используют нестабильность частот сейш - кратковременную фазомодулированную, длительную частотно-модулированную. Purpose. The purpose of the paper is to demonstrate the application of seiches oscillations of the water mass with unstable but manageable frequency in seismic tomography, which eliminates the excitation of elastic waves requiring expensive percussion, explosion and vibration technologies; to develop methods for seismic tomography using the property of sweep- frequency seiches.
Design/methodology/approach. We discovered that frequency of seiches depends on water level as well as on the phase of stimulation wave. These properties were then used in methods for conducting seismic raying of the earth's crust.
Findings. On the example of Lake Sevan, it was shown that depth-sweep of water, which changes the level from minimum to maximum and back, causes a corresponding long-term frequency-modulated sweep of seiches. On the example of Aral Sea, we showed that the phase shift of exciting wave with respect to the decaying seiche leads to a short-term phase- modulated sweep of a resulting wave.
Practical value/implications. We justified the advantages of seismic tomography using seiches: seiches allow man-made oscillation; microseisms of seiches origin are characterized by a long range; seiches modulate high-frequency microseisms, which allows us to interpret them jointly and to increase reliability of the received seismic signal; seiches allow controlled frequency sweep, making it possible to record the frequency response of an object environment.